Improved Algorithm to Detect Fluid Accumulation via Intrathoracic Impedance Monitoring in Heart Failure Patients With Implantable Devices - Sarkar, Shantanu; Hettrick, Douglas A.; Koehler, Jodi; Rogers, Tyson; Grinberg, Yanina; Yu, Cheuk-Man; Abraham, William T.; Small, Roy; Tang, W.H.Wilson (Journal of cardiac failure, 2011)
Intrathoracic impedance fluid monitoring has been shown to predict worsening congestive heart failure (CHF) in patients with implantable devices. We developed and externally validated a modified algorithm to identify worsening heart failure (HF) by using intrathoracic impedance. The modified algorithm was developed by using published data from 81 CHF subjects averaging 259 days of follow-up. Device-measured daily impedance was input to both the existing and the modified intrathoracic impedance fluid monitoring algorithms to determine a reference impedance and a fluid index (FI). Separate validation sets included 326 cardiac resynchronization therapy device (CRT-D) patients with an average 333 days of follow-up (group 1) and 104 CRT-D/implantable cardioverter/defibrillator (ICD) patients followed for an average of 520 days (group 2). Clinicians and patients in group 2 were blinded to impedance and FI data. HF events included adjudicated HF hospitalizations or emergency room visits. Sensitivity was defined as the percentage of HF events preceded by FI exceeding the predefined threshold (60 Ω-d) within the last 2 weeks. Unexplained detections were FI threshold crossing events not followed by a HF event within 2 weeks. The modified algorithm significantly decreased unexplained detections by 30% ( P = .01; GEE) in the development set, 30% ( P < .001) in the group 1 validation set, and 43% ( P < .001) in group 2. Sensitivity did not change significantly in any group. Simulated monthly review of FI threshold crossings identified subjects at significantly greater risk of worsening HF within the next 30 days. A modified intrathoracic impedance based fluid detection algorithm lowered the number of unexplained FI threshold crossings and identified patients at significantly increased immediate risk of worsening HF.